2001
DOI: 10.1063/1.1409368
|View full text |Cite
|
Sign up to set email alerts
|

Time-averaged hydrodynamic roughness of a noncolloidal sphere in low Reynolds number motion down an inclined plane

Abstract: A system consisting of a spherical particle in motion down an inclined planar surface in a viscous liquid was investigated theoretically and experimentally to examine the effects of surface roughness on the interactions between the sphere and the plane. Two characteristic roughness scales were used to describe the microscopic surface roughness of the sphere. The smallest roughness elements are assumed to dominate the surface, and the largest roughness elements are more sparse. The time-averaged nominal separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
38
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 20 publications
4
38
2
Order By: Relevance
“…[8][9][10]12 Many of these previous studies have demonstrated the importance particle surface roughness in relieving the lubrication singularity of spheres at contact. 9,11 The flattening of a liquid drop adherent on a wall in shear flow 14 is relevant to leukocyte adhesion at much higher shear stresses than studied here ͑ ϳ 10 dyn/ cm 2 ͒, when significant deformation of the cell occurs. In a work closely related to the present study, Chapman and Cokelet 15 calculated the drag force on multiple spheres adherent on the wall of a tube; however, they did not consider any motion of the spheres.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…[8][9][10]12 Many of these previous studies have demonstrated the importance particle surface roughness in relieving the lubrication singularity of spheres at contact. 9,11 The flattening of a liquid drop adherent on a wall in shear flow 14 is relevant to leukocyte adhesion at much higher shear stresses than studied here ͑ ϳ 10 dyn/ cm 2 ͒, when significant deformation of the cell occurs. In a work closely related to the present study, Chapman and Cokelet 15 calculated the drag force on multiple spheres adherent on the wall of a tube; however, they did not consider any motion of the spheres.…”
mentioning
confidence: 78%
“…Several recent fluid mechanical studies have examined the interaction of small particles with a planar wall, [8][9][10][11][12][13] however, none of these have focused on the adhesive rolling motion of spheres along the wall of a circular tube. In our system, characteristic Reynolds numbers based on the leukocyte radius are O͑10 −3 ͒, so that inertial effects are expected to be negligible.…”
mentioning
confidence: 99%
“…Furthermore, surface contact (D = δ) introduces a non-hydrodynamic frictional resistance to particle motion. Problems involving the rolling of a sphere down an inclined plane immersed in a viscous liquid have been addressed in earlier studies [33,34] in which the normal force between the particle and the surface was due to gravity, and the contact between surface roughness elements present on the surface gave rise to a non-hydrodynamic resistive force. The present analysis extends this work to a neutrally buoyant particle experiencing a spatially varying normal force due to the physicochemical interactions between the particle and the nanotextured wall.…”
Section: Contact/frictional Forcesmentioning
confidence: 99%
“…Although subjected to a lift force, the particles will still remain in virtual contact with the incline. The torque balance and rotation of the particles (Galvin et al, 2001) are neglected given that most "real" particles have an irregular geometry and therefore resist any tendency to rotate, preferring to slide.…”
Section: Theoreticalmentioning
confidence: 99%